Synthesis, photophysical, electrochemical and electroluminescence studies of red emitting phosphorescent Ir(III) heteroleptic complexes - Ali, F; Nayak, P; Periasamy, N; Agarwal, N (Springer, 2017)
Five heteroleptic, cyclometalated (C∧N) Iridium(III) complexes of acetylacetone (acac) and 1-phenyl-isoquinoline (piq) derivatives, Ir(acac)(piq)2, Ir(acac)(2,4-difluoro-piq)2, Ir(acac)(4-trifluoromethyl-piq)2, Ir(acac)(4-N,N-dimethyl-piq)2, Ir(acac)(4-acetyl-piq)2, were synthesized and characterized. The (C∧N)2Ir(acac) complexes in toluene showed phosphorescence (λmax=598 nm to 658 nm) with quantum yields (0.1 to 0.32) and microsecond lifetimes (0.43 to 1.9 μs). The complexes were non-luminescent in thin films due to self-quenching but luminescent when lightly doped (5%) in a host organic material, 4,4′-Bis(N-carbazolyl)-1,1′-biphenyl (CBP). The HOMO levels determined using cyclic voltammetric oxidation potentials were in the range −5.48 to −5.80 eV. Electroluminescence properties and performance of the Ir complexes doped in CBP (active layer) were studied in a multilayer (ITO/F4TCNQ/TPD/doped CBP/BCP/LiF/Al) organic light emitting device (OLED). The electroluminescense (EL) spectra of the device matched with the phosphorescent spectra of the Ir complexes. The turn-on voltage at ∼4.5 V, maximum brightness of 7600 cd/m2 and current efficiency of ∼7.0 cd/A at a brightness of ∼100 cd/m2 indicate that these are promising OLED materials.